2020
DOI: 10.1017/s0016756820000291
|View full text |Cite
|
Sign up to set email alerts
|

Phased evolution and variation of the South Asian monsoon, and resulting weathering and surface erosion in the Himalaya–Karakoram Mountains, since late Pliocene time using data from Arabian Sea core

Abstract: We investigate the phased evolution and variation of the South Asian monsoon and resulting weathering intensity and physical erosion in the Himalaya–Karakoram Mountains since late Pliocene time (c. 3.4 Ma) using a comprehensive approach. Neodymium and strontium isotopic compositions and single-grain zircon U–Pb age spectra reveal the sources of the deposits in the east Arabian Sea, and show a combination of sources from the Himalaya and the Karakoram–Kohistan–Ladakh Mountains, with sediments from the Indian Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…They noted that sandy turbidite deposits tended to be associated with high 87 Sr/ 86 Sr ratios and low ɛ Nd values, likely linked to erosion from the Himalayas and delivered by the Indus River. As in the Kumar et al (2019) and Lu et al (2020) studies, they propose that sea level plays a critical role in controlling sediment flux into the basin.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…They noted that sandy turbidite deposits tended to be associated with high 87 Sr/ 86 Sr ratios and low ɛ Nd values, likely linked to erosion from the Himalayas and delivered by the Indus River. As in the Kumar et al (2019) and Lu et al (2020) studies, they propose that sea level plays a critical role in controlling sediment flux into the basin.…”
mentioning
confidence: 84%
“…Change in the source of siliciclastic material to the submarine fan was reconstructed since 3.4 Ma by Lu et al (2020) using a combination of neodymium and strontium isotopes, together with single-grain zircon U–Pb age data. These authors show that the sediments represent a combination of erosion from the Himalayas, Karakoram and Kohistan–Ladakh, as well as some sediment flux from the peninsula of India, including the Deccan Traps and Indian Craton.…”
mentioning
confidence: 99%
“…In addition, the glacial-interglacial cycles lead to sea level fluctuations, such as the extensive exposure of marginal sea shelf during the glacial period, which may affect the spatial distribution pattern of precipitation in the provenance (Cai et al, 2015). Moreover, the changes of local ocean currents and shelf material transport in glacial-interglacial cycles may also lead to local environmental variations in marine sediments (Wang et al, 2014;Lu et al, 2020). Thus, how to effectively separate the temperature signals from the geological record of the summer monsoon is still worthy of further study.…”
Section: Proxies and Paleo-monsoon Variability 21 Monsoon Proxiesmentioning
confidence: 99%
“…The influence of Earth orbital forcing on the long-term evolution of Indian monsoon has been recorded in deep-sea cores, lake sediments and stalagmites (Ziegler et al, 2010a;Cai et al, 2010;An et al, 2011). Previous researches demonstrated that the climate evolution of Indian monsoon is dominated by precession (~23 ka), obliquity (~41 ka) and eccentricity (~100 ka) cycles (e.g., Clemens et al, 1996;Clemens and Prell, 2003;Kelly et al, 2005;Kunkelova et al, 2018;Lindhorst et al, 2019;Lu et al, 2020). Previous orbital-scale studies of the ISM mainly used proxies of phytoplankton (G. bulloides) from the northern Arabian Sea (Prell et al, 1984;Prell and Van Campo, 1986;, grain size (Clemens and Prell, 1990;Krissek and Clemens, 1992), Ti/Al and excess Ba MAR (Shimmield et al, 1990), biogenic opal and organic carbon MAR (Murray and Prell, 1991).…”
Section: Orbital-scale Variabilitymentioning
confidence: 99%
“…Thus, the East Asian monsoon region provides an ideal case for revealing intriguing and complex tectonic-climate interactions. For example, many previous studies have investigated Asian monsoon development with changes in Neogene mountain exhumation, silicate weathering, and the associated CO 2 consumption (e.g., Clift et al, 2008Clift et al, , 2014Lu et al, 2020;Van Hoang et al, 2010;Wan et al, 2012). In particular, the Chinese Loess Plateau (CLP) in north China, an area that is very sensitive to variations in the East Asian summer and winter monsoons, has accumulated long, continuous eolian sequences within the large platforms on the eastern portion of the plateau (An et al, 2001).…”
mentioning
confidence: 99%